Analysis of Lattice Temperature in Super Junction Trench Gate Power MOSFET as Changing Degree of Trench Etching - Lee, Byeong-il; Geum, Jong Min; Jung, Eun Sik; Kang, Ey Goo; Kim, Yong-Tae; Sung, Man Young (IEEK PUBLICATION CENTER, 2014)
Super junction trench gate power MOSFETs have been receiving attention in terms of the trade-off between breakdown voltage and on-resistance [1]. The vertical structure of super junction trench gate power MOSFETs allows the on-resistance to be reduced compared with conventional Trench Gate Power MOSFETs. The heat release of devices is also decreased with the reduction of on-resistance. In this paper, Lattice Temperature of two devices, Trench Gate Power MOSFET and Super junction trench gate power MOSFET, are compared in several temperature circumstance with the same Breakdown Voltage and Cell-pitch. The devices were designed by 100V Breakdown voltage and measured from 250K Lattice Temperature. We have tried to investigate how much temperature rise in the same condition. According as temperature gap between top of devices and bottom of devices, Super junction trench gate power MOSFET has a tendency to generate lower heat release than Trench Gate Power MOSFET. This means that Super junction trench gate power MOSFET is superior for wide-temperature range operation. When trench etching process is applied for making P-pillar region, trench angle factor is also important component. Depending on trench angle, characteristics of Super junction device are changed. In this paper, we focus temperature characteristic as changing trench angle factor. Consequently, Trench angle factor don't have a great effect on temperature change.